气缸套激光表面硬化指标的神经网络预测 - 任菲; 吴耀宇; 吴晓铃; 赵少甫 (Jixie chuandong)
Based on the data obtained from the perpendicular experiment of laser surface hardening on HT150 cylinder liner of a certain motor engine,and with BP neural network’s powerful function in numeric forecast,a neural network forecast model of laser surface hardening index about HT150 cylinder liner is established.The convergence speed is accelerated and the prediction accuracy of the hardening index is improved by adjusting the number of hidden-layer neurons in the network.